THE DIGITALIZATION OF PUBLIC ADMINISTRATION IN KOSOVO: CHALLENGES, OPPORTUNITIES AND THE IMPACT ON THE QUALITY OF PUBLIC SERVICES - Milot KRASNIQI; Zemri ELEZI; Dardan VUNIQI (PRIZREN SOCIAL SCIENCE JOURNAL, 2026)
The digitalization of public administration is today considered one of the main instruments for increasing efficiency, transparency and accountability in the public sector. This paper examines the process of digitalization of public administration in the Republic of Kosovo, analyzing the legal and strategic framework, the integrated e-Kosova platform, as well as the factors influencing the acceptance and use of electronic services by citizens. The paper is based on a mixed-methods methodological approach, which combines the analysis of documents and secondary data (reports of the Ministry of Public Administration, the E-Governance Strategy 2023–2027, reports of the International Monetary Fund and of non-governmental organizations) with a conceptual framework based on the Unified Theory of Acceptance and Use of Technology (UTAUT). The results show that, despite notable progress in expanding the portfolio of electronic services offered through the e-Kosova platform, the level of effective use by citizens remains below its real potential, mainly due to a lack of institutional trust, limited digital skills, challenges of interaction between systems (interoperability) and cyber insecurity. The paper concludes with a set of recommendations for policymakers, emphasizing the need to strengthen digital infrastructure, increase the digital literacy of the population and consolidate the legal framework for data protection.